Memutus Rantai Isolasi: Efektivitas TAKS dalam Membangun Kembali Interaksi Sosial Pasien - Fredy Akbar K; Ashriady Ashriady; Aswat Aswat; Musdalifah Musdalifah; Nurul Aeni (Jurnal Pengabdian Masyarakat JUPEMANDO, 2025)
This activity aims to increase social interaction and socialization of socially isolated patients through Socialization Group Activity Therapy (TAKS). The case study method was applied to 8 adult male patients at RSKD Dadi Makassar for two weeks in seven structured TAKS sessions. Results showed a significant improvement in patients' verbal communication skills, including introducing themselves, getting acquainted, conversing, and cooperating. The majority of patients showed verbal improvement (87.5%), while active nonverbal participation was 75%. However, the use of appropriate body language was still low (0%), indicating an increase in verbal dominance. The client's social isolation is dominated by psychological factors (unpleasant experiences, emotional trauma). TAKS has been shown to be effective in reducing symptoms of social isolation and gradually improving patients' social skills. Therefore, TAKS is recommended as an integral intervention in psychiatric rehabilitation. For sustainability and improved outcomes, more intensive nonverbal exercises are recommended as well as further research on the integration and long-term effectiveness of TAKS.